HUBUNGAN PERSEPSI TERHADAP KOMPENSASI DENGAN KEPUASAN KERJA PADA KARYAWAN BAGIAN MARKETING - Irvan Hilmi, - (2010)
This research based on phenomenon the importance of work of employee at part of marketing in the relation with perception to compensation and job satisfaction. Where there is estimation that perception of compensation correlates positively with job satisfaction of employee. This research inter alia aim to know: (1) As perception to compensation at employee part of marketing, (2) As job satisfaction at employee part of marketing, and (3) How big relation between perception to compensation with job satisfaction at employee part of marketing. Perception to compensation is assessment of employee individually felt to reward in the form of financial and or nonfinansial received by it instead of their contribution to companies. While job satisfaction is positive emotion or feeling likes, as result from assessment of someone to the work or job experience. This research design haves the character of correlational by using survey methode. Subject that is accurate is all employee at part of marketing in PT. Global Persada Farma Kota Bandung. Instrument applied is perception questionaire to compensation developed based on the compensation theory from Buchari and instrument of job satisfaction developed based on the job satisfaction theory from Locke, with is in the form of scale Likert which its each having level of reliability 0933 and 0927. At result of research it is obtained that: (1) In general employee has perception which are positive to compensation, (2) In general employee has level of job satisfaction residing in at satisfied katagori, and (3) Degree of correlation 0686 menunjukan meaning of that there is relationship which are positive and strong between independent variables to variable dependen.